INCORPORATING INCLUSIVE ASSESSMENT PRINCIPLES AND UNIVERSAL DESIGN FOR LEARNING IN ASSESSING MULTICULTURAL CLASSROOM: AN AUTOETHNOGRAPHY - Kusumaningsih, Sisilia Novena (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Teaching a multicultural classroom has always been challenging for educators. With the rush toward global standardization, there is a concern that uniformity in education will sacrifice students’ freedom in expressing their skills and knowledge. This problem can be seen in the way students are being assessed. The rapid growth of standardized tests and the demand to meet yearly progress thresholds are tangible examples of how assessments may limit the way students demonstrate their learning attainment. This article aims at presenting several alternatives teachers could take to implement Universal Design for Learning (UDL) and inclusive assessment principles in assessing multicultural classrooms. This analytic autoethnography study yielded three themes: providing options of assessment forms, providing accommodation in conducting assessments, and using the strength-based language in assessment feedback.